THE IMPLEMENTATION OF A CLEAN AND HEALTHY LIFESTYLE ON YOUNG CHILDREN AT PRIMA SAKINAH KINDERGARTEN - Binawanti, Arsi (Journal of Early Childhood Education (JECE), 2021)
A Clean and Healthy Lifestyle needs to be accustomed from an early age so that children are maximally stimulated and away from disease. The purpose of this study was to find out in detail the clean and healthy lifestyle program implemented by Prima Sakinah Kindergarten and its supporting sanitation facilities and infrastructure. Prima Sakinah Kindergarten is one kindergarten that has implemented a Clean and Healthy Lifestyle Habituation program since 2003. Prima Sakinah Kindergarten also won first place in Healthy Schools at the Mustika Jaya district level, Bekasi. It became one of the early childhood education institution-level driving schools representing Bekasi. The method used in this research is naturalistic qualitative with data collection and data analysis using interview, observation, and documentation studies. The research subjects were 25 students of Prima Sakinah Kindergarten. Prima Sakinah Kindergarten implements the Clean and Healthy Lifestyle program well. The program includes washing hands with soap and running water, habituation of tooth brushing, urinating and defecating in the latrine, clipping nails, eating healthy, balanced, and nutritious food, water therapy, giving milk, disposing of garbage in its place, and sorting out waste, physical activity, and monitoring children's growth.